URGENSI PENDIDIKAN AGAMA ISLAM DI KELUARGA DALAM MENGATASI KENAKALAN REMAJA PADA SISWA MADRASAH ALIYAH (MA) KANJENG SEPUH GRESIK - Mashuri, Imam; Afifah, Afifah (INCARE, International Journal of Educational Resources, 2021)
A child's education will not be separated from the role of parents, family is the foundation of child education, school is just a complement. If the child lives in a family environment that understands Islamic religious education then we will get a child who is far from juvenile delinquency, and vice versa. Therefore, the purpose of this writing is to know the influence of Islamic religious education in the family in overcoming juvenile delinquency in MA Kanjeng Sepuh Gresik students, using a type of field research, while the approach used is a quantitative descriptive approach method. In this study the population is all students of Madrasah Aliyah (MA) Kanjeng Sepuh Gresik, while the sample is students of grade XI Madrasah Aliyah (MA) Kanjeng Sepuh Gresik. The technique of collecting research data is to use interview methods, questionnaires, and documentation. While the data analysis in this study is using product moment correlation. The results showed that the urgency of Islamic religious education in the family is quite good, this was obtained from the results of a questionnaire on Islamic religious education in the family that was analyzed through percentage and produced a score of 67.66%. Family results in overcoming juvenile delinquency in MA Kanjeng Sepuh Gresik students are relatively good, this is known from the frequency of grades belonging to the category of completion as many as 34 students out of a total of 34 students or by 100%.